Cover Feature: Like‐likes‐Like: Cooperative Hydrogen Bonding Overcomes Coulomb Repulsion in Cationic Clusters with Net Charges up to Q=+6e (ChemPhysChem 14/2018). Issue 14 (2nd July 2018) - Niemann, Thomas; Stange, Peter; Strate, Anne; Ludwig, Ralf
Abstract : The Cover Feature visualizes how hydrogen bonding can overcome Coulomb repulsion in clusters of like‐charged ions. In their communication Ludwig et al. report kinetically stable cationic clusters with a high net charge up to Q =+6 e . Despite strongly repulsive Coulomb forces, the hydroxy‐functionalized N‐(3‐hydroxypropyl)pyridinium cations are trapped by hydrogen bonding in a cyclic hexamer. More information can be found in the Article by R. Ludwig et al. on page 1691 in Issue 14, 2018 (DOI: 10.1002/cphc.201800293 ).